Metode Tuan Guru Metode TGH. Syahri Ramadhan dalam membina akhlak santri: Studi di Ponpes Darul Musthofa NW Keru - muhammad yuslih yuslih; Bahroni Zainuri Yulien (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This article discusses the master teacher Syahri Ramadhan as the leader of the Darul Muthofa NW Keru Islamic boarding school, as well as being the leader of the master teacher, Syahri Ramadhan being the central point in fostering morals. In this study, the researcher wanted to see what methods were used by the master teacher Syahri Ramadhan in building the morals of the Darul Musthofa NW Keru Islamic boarding school students, as well as what obstacles were faced in applying the methods used in building the morals of the students. As for this study, researchers used qualitative methods, while the data collection techniques used in this study were observation, interviews, and documentation. The results of this study indicate that there are several methods used by the master teacher Syahri Ramadhan in fostering the morals of students, namely, exemplary, habituation, health and punishment and reward. In addition, there are two inhibiting factors in building the morals of students, namely family environmental factors and social factors.